Mothers levels of knowledge of self-medication of diarrhea for under-five children in Kaliwates, Jember - Inasa Hazrina; Sinta Rachmawati; Ema Rachmawati (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Diarrhea is the fifth-highest cause of death in under-five children worldwide, and it is preventable. Mild diarrhea can be treated by self-medication. In this case, mothers have an important role in handling diarrhea in children. This study aims to determine the level of mothers knowledge self-medication in diarrhea to treat under-five children in Kaliwates District, Jember. This study used an observational study design with a cross-sectional approach. The data were collected in 11 integrated healthcare centers in 3 community health centers in Kaliwates District. The research respondents were 348 mothers. Before being distributed, the questionnaire was tested to explore its validity and reliability. This questionnaire was employed to assess the mothers' level of knowledge of self-medication for infants. The data were analyzed statistically using the Chi-square test and Fisher Exact. The results showed that the mothers have a sufficient of knowledge level self-treatment of diarrhea for infants. There is a significant relationship between age, recent education, employment, family income, number of children, number of adult family members, information sources, and educational experience (p < 0.05). This study suggests the importance of providing interventions to improve mothers knowledge of self-medication of diarrhea.